The Relationship of Service Quality, Patient Safety, and Patient Trust with Patient Satisfaction at Bhayangkara Hospital Surakarta - Retna Wiyarti (Indonesian Journal of Innovation Science and Knowledge, 2026)
Patient satisfaction is a key indicator of hospital service quality and is influenced by service quality, patient safety, and patient trust. Internal surveys at Bhayangkara Hospital Surakarta showed that patient satisfaction had not yet reached the institutional target, highlighting the need to identify factors associated with satisfaction. This study aimed to analyze the relationships between service quality, patient safety, patient trust, and patient satisfaction, and to determine the dominant contributing factorAn observational analytic study with a cross-sectional design was conducted from May to June 2026. A total of 186 outpatients and inpatients were selected using purposive sampling. Data were collected using validated and reliable questionnaires and analyzed using descriptive statistics, Spearman Rank correlation, and multiple linear regression. Most respondents rated service quality as good (72.0%), patient safety as safe (66.1%), patient trust as high (74.7%), and patient satisfaction as satisfactory (62.4%). Service quality (r=0.199; p=0.007), patient safety (r=0.304; p<0.001), and patient trust (r=0.150; p=0.041) were significantly associated with patient satisfaction. Multiple regression analysis showed that the three variables jointly influenced patient satisfaction (F=11.245; p<0.001; Adjusted R²=0.142), with patient safety identified as the strongest predictor. Strengthening patient safety, improving service quality, and fostering trust are essential strategies for enhancing patient satisfaction in hospitals.